المفردات الاصطلاحية في كتاب منحة العلام للمستوى السابع والاستفادة منها في إثراء لغة الطالبات بجامعة الراية - WILDA FAHRAIN NURILLAH; ARIF TAUFIQURRAHMAN (Rayah Al-Islam, 2016)
The terms have an important role to improve four language skills for a language learner. Since it was not controlled by the learners, it would be difficult to apply those skills. This study aims to analyze the terms contained in Minhati Al-‘Allâm's book for the seventh semester students and their application on the enrichment for students of STIBA Ar-Raayah. And to help students in memorizing the vocabularies of the terms, the researcher suggests either for teachers or students of Arabic to make a special table contained in the terms along with the meaning of the terms arranged in alphabetical letters. The method used by the researcher in completing the research is a descriptive method. The first step taken by the researcher was to search for vocabulary that contains the meaning of and terms in the seventh semester Minhati Al-'Allâm book, then write the meaning and terms of the vocabulary, give suggestions for making vocabulary tables to facilitate students in learning Arabic, and provides the following conversational texts and reading texts with the completion of exercises related to this to find out the level of understanding and the quality of students' language in Arabic. The results of this study indicate that there are 149 terms contained in Minhati Al-‘Allâm's book on the seventh semester students. But the researcher have analyzed 83 terms, in which teachers and students of arabic can use in the learning process of the language.